PERAN ORANG TUA DALAM MENGENALKAN ANGGOTA TUBUH PADA ANAK USIA PRASEKOLAH DENGAN AUTISTIK - Anggraini, Diah Retno (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2018)
The rise of cases of sex exploitation in children is a clear proof of the lack of knowledge of children about sex education that they should have obtained from the first year by their parents. Entering the age of 1-2 years, the ability to speak, curiosity, and the ability to remember began to increase and quite well. Now is the right time to continue adding vocabulary and hone the child's ability to remember and speak, by starting to introduce body parts like hair, nose, knees, heels, and so on. Autism is a term used to describe a type of pervasive disorder in a child that results in a disturbance or delay in cognitive, language, behavioral, communication and social interaction. Providing education and understanding is a challenge for parents themselves. This study illustrates how the roles performed and displayed by individual autistic parents in introducing body parts. The method used in this study is a qualitative method with a case study approach with observations and interviews conducted to parents of individuals with autism. The results of this study indicate that the maximal parental role produces autistic autonomous individual behavior. Independent in terms of understanding the body parts, maintaining the hygiene of the body parts and understanding the body parts that can be touched and not touched.Keywords: Autistic, Preschool age, Body Parts, Parents